Improving Healthcare Services Using Clinical Decision Support Systems: A Systematic Review - Daniel Iskandar; Wahyu Adi Setyo Wibowo; Gandung Triyono (Universitas Pahlawan Tuanku Tambusai, 2022)
Patient safety and recovery is the main objective in healthcare. The knowledge and experiences of medical experts and patient big data can be transformed into a Clinical Decision Support System that will deliver benefits to healthcare, especially for the patients. This research is a literacy review that aims to create a framework for reviewing articles on DSS which highly related to patients, which were published by Elsevier from 2017 to October 2022. There were 29 articles found from search results on Elsevier, of which 13 were research articles. After conducting analysis and filtering, we found 6 articles that met the criteria for research objects that examined several DSS topics, namely Pre-hospital Decision Support Tools, Patient Referral, Antimicrobials, Patient Nutrition, and Blood Transfusion. The results of this study showed that DSS implementations in healthcare give a huge impact on medical experts, namely by providing important information for decision-making when treating patients. This enables the hospitals and medical team to provide appropriate therapy from the beginning of the treatment and it increased the success of patient therapy possibility. Another benefit is the medical cost saving since the therapies are only given when it is needed by the patient.